Global virtual work: a review, integrative framework, and future research opportunities - Fabian Jintae Froese; Tobias Blay; Cristina B. Gibson; Margaret A. Shaffer; Jose Benitez (Journal of International Business Studies, 2025)
Digitalization and global disruptions have fundamentally changed how we approach work. Global virtual work has become increasingly widespread in recent years, often replacing or complementing traditional expatriation and international business travel. To advance our understanding of this phenomenon, we systematically reviewed the literature on global virtual work, distinguishing it into three domains: global virtual teams, distributed work, and the use of digital technologies. For each domain, we examined key actors, their objectives, underlying theories, methodologies, and findings. The first domain provides insights into the antecedents, moderators, and mediators of the effectiveness of global virtual teams. The second domain explores individual and organizational research on diverse distributed work arrangements, such as offshoring, global platforms, and global nomads. The third domain addresses the enabling and moderating roles that digital technologies play in facilitating global virtual work. Synthesizing prior research, we developed a multilevel conceptual framework that integrates inputs, processes, and outcomes of global virtual work, offering novel perspectives. We outlined promising opportunities for future research across four themes: people, technology, context, and time. Additionally, we examined the practical implications of our findings for policymakers, managers, and individual workers as they navigate the evolving landscape of global virtual work.
Keywords: 330; Global virtual work; Global virtual teams; Distributed work; Digital technologies; Global nomads; Gig workers; Systematic literature review; Multilevel model; Future research opportunities